Inorganic coated sand and method for producing the same, inorganic coated sand composition, and casting mold
Inorganic coated sand with a metasilicate hydrate-based binder layer and amorphous SiO2 fine particles addresses storage stability and mechanical strength issues, enabling stable mold production.
Patent Information
- Application Number
- JP2024092070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-08
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional inorganic coated sands suffer from poor storage stability and mechanical strength issues, leading to mold manufacturing failures.
The development of inorganic coated sand with a specific metasilicate hydrate-based inorganic binder layer, having controlled melt viscosity, hydration amount, and melting point, which includes amorphous SiO2 fine particles, ensuring both good storage stability and mechanical strength.
The solution provides inorganic coated sand with improved mechanical strength and storage stability, allowing for effective mold production without wetting during storage.
Smart Images

Figure 2024177122000001 
Figure 2024177122000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic coated sand and a method for producing the same, an inorganic coated sand composition, and a casting mold. [Background technology]
[0002] As a mold used for casting of castings, for example, one obtained by molding into a desired shape using inorganic coated sand having refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate is known. Examples of technologies relating to such inorganic coated sand include those described in Patent Document 1 (International Publication No. 2018 / 097180), Patent Document 2 (JP Patent Publication No. 53-025803), and Patent Document 3 (JP Patent Publication No. 2020-11296).
[0003] Patent Document 1 discloses coated sand in a dry state having fluidity at room temperature, in which the surface of a fire-resistant aggregate is covered with a coating layer containing water glass, and the coating layer contains spherical particles.
[0004] Patent Document 2 describes a method for producing a mold, which comprises adding an alkali metasilicate solution prepared by adding a caustic alkali to water glass to refractory particles such as silica sand and kneading the solution with the refractory particles, or further adding an alcohol during kneading, thereby precipitating and coating a crystalline alkali silicate on the surfaces of the refractory particles such as silica sand, and then adding and mixing fine dust generated during Fe-Si refining and composed mainly of SiO2 to produce a powder-and-granular mixed sand, which is then heated to at least the melting point of the crystalline alkali silicate and hardened.
[0005] Patent Document 3 discloses a dry inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, in which the inorganic binder layer contains at least one type of metasilicate hydrate selected from sodium metasilicate pentahydrate and sodium metasilicate nonahydrate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2018 / 097180 [Patent Document 2] Special Publication No. 53-025803 [Patent Document 3] JP 2020-11296 A Summary of the Invention [Problem to be solved by the invention]
[0007] According to the inventor's research, the conventional inorganic coated sands disclosed in Patent Documents 1 to 3 become wet during storage, and there are cases where a mold cannot be manufactured thereafter. On the other hand, it has been found that even if the storage stability of the inorganic coated sand is good, the mechanical strength of a mold made using the inorganic coated sand may not be sufficient. In other words, the present invention relates to achieving both higher storage stability in dry inorganic coated sand and improved mechanical strength of a mold made from the coated sand after storage. [Means for solving the problem]
[0008] The present inventors have conducted studies from the viewpoint of achieving both the storage stability of inorganic coated sand and the mechanical strength of a mold made from the coated sand after storage. As a result, they have found that it is effective to set the melt viscosity of the inorganic binder in the inorganic binder layer within a specific range, to set the amount of water of hydration of the metasilicate hydrate in the inorganic binder layer within a specific range, and to have the inorganic coated sand have a fusion point of 40° C. or more and 60° C. or less as measured in accordance with JACT Test Method C-1 Fusion Point Test Method, and have completed the present invention.
[0009] According to the present invention, A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic coated sand is provided, in which the inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, and the inorganic binder constituting the inorganic binder layer has a melt viscosity at 80°C of 32 mPa s or more and 150 mPa s or less.
[0010] Further, according to the present invention, A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic coated sand is provided, in which the inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, and the metasilicate hydrate has an amount of water of hydration of 6 or more and 8 or less.
[0011] Further, according to the present invention, A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, Inorganic coated sand is provided that has a fusion point of 40°C or more and 60°C or less according to JACT Test Method C-1 Fusion Point Test Method.
[0012] The present invention also provides an inorganic coated sand composition containing the above-mentioned inorganic coated sand.
[0013] The present invention also provides a casting mold using the above-mentioned inorganic coated sand.
[0014] The present invention also provides a casting mold using the above-mentioned inorganic coated sand composition.
[0015] Further, according to the present invention, A method for producing dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, comprising: (1) mixing the refractory aggregate, metasilicate nonahydrate, and metasilicate pentahydrate to obtain a mixture; (2) cooling the mixture; Including, The step (1) includes mixing the metasilicate nonahydrate and the metasilicate pentahydrate at a temperature equal to or higher than the melting point of the mixture, The step (2) includes cooling the mixture of the metasilicate nonahydrate and the metasilicate pentahydrate to a temperature lower than the melting point of the mixture, thereby providing a method for producing an inorganic coated sand.
[0016] Further, according to the present invention, The method for producing the inorganic coated sand described above comprises the steps of: (3) mixing the refractory aggregate with a solution containing water glass, caustic alkali, and water to obtain a mixture containing metasilicate hydrate; A method for producing an inorganic coated sand is provided, comprising: Effect of the Invention
[0017] According to the present invention, it is possible to provide inorganic coated sand which can improve the mechanical strength of a mold using the same while maintaining good storage stability of the inorganic coated sand. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present invention will be described. In addition, in this specification, "A to B" indicating a numerical range means a range from A to B, including both ends, unless otherwise specified. In addition, the components and elements described in each embodiment can be appropriately combined as long as the effect of the invention is not impaired.
[0019] <Inorganic coated sand> The inorganic coated sand of the present embodiment is a dry inorganic coated sand containing a refractory aggregate and an inorganic binder layer covering the surface of the refractory aggregate, the inorganic binder layer containing metasilicate hydrate and amorphous SiO2-containing fine particles, and satisfying at least one of the following (i) to (iii): (i) the inorganic binder constituting the inorganic binder layer has a melt viscosity at 80°C of 32 mPa s or more and 150 mPa s or less; (ii) the amount of water of hydration of the metasilicate hydrate is 6 or more and 8 or less; (iii) The fusion point of the inorganic coated sand, as determined in accordance with JACT Test Method C-1 Fusion Point Test Method, is 40°C or higher and 60°C or lower. This makes it possible to achieve both good storage stability of the dry inorganic coated sand containing refractory aggregate and an inorganic binder layer covering the surface of the refractory aggregate, and good mechanical strength of a mold using the same.
[0020] First, in the inorganic coated sand of this embodiment, the metasilicate constituting the inorganic binder layer is a hydrate. This improves the crystallinity of the inorganic binder layer, and the inorganic coated sand is in a dry state, which makes it excellent in room temperature fluidity and improves the strength of the mold using the inorganic coated sand. Furthermore, the inorganic binder layer further contains amorphous SiO2-containing fine particles, which allows the particles of the inorganic coated sand to be more firmly bonded to each other via the amorphous SiO2-containing fine particles, making it easier to improve the strength of the mold.
[0021] In addition, in the inorganic coated sand of this embodiment, (i) the melt viscosity at 80°C of the inorganic binder constituting the inorganic binder layer is set to 32 mPa·s or more and 150 mPa·s or less. This is thought to contribute to improving the mechanical strength of a casting mold using the inorganic coated sand by causing the inorganic binder to aggregate at the bonding points between the inorganic coated sand particles when the inorganic binder layer melts to form an adhesive layer, and also to prevent the inorganic coated sand from becoming too reactive with other components, such as refractory aggregates and amorphous SiO2-containing fine particles, and becoming easily wet.
[0022] On the other hand, in the inorganic coated sand of this embodiment, (ii) the amount of water of hydration of the metasilicate hydrate can be set to 6 or more and 8 or less.
[0023] Here, the inventors have found that the amount of hydration water of metasilicate hydrate affects the mechanical strength of the mold and the storage stability of the inorganic coated sand. Specifically, it has been found that the greater the amount of hydration water of metasilicate hydrate, the more likely the inorganic coated sand becomes wet during storage, while the mold strength immediately after the inorganic coated sand is produced tends to be higher. Although the details of the mechanism are not clear, it has been speculated that the greater the amount of hydration water of metasilicate hydrate, the higher the reactivity with other components such as refractory aggregates and amorphous SiO2-containing fine particles, resulting in the more likely the sand becomes wet, but the more likely the mechanical strength is to be improved. Thus, in the inorganic coated sand of this embodiment, the amount of water of hydration of the metasilicate hydrate is preferably 6 or more, thereby improving the mechanical strength of the mold, while the amount of water of hydration of the metasilicate hydrate is preferably 8 or less, thereby improving the storage stability of the inorganic coated sand while maintaining good mechanical strength of the mold. More specifically, even when compared with inorganic coated sand using the same refractory aggregate, the inorganic coated sand of this embodiment, by setting the amount of water of hydration of the metasilicate hydrate to 6 or more and 8 or less, can achieve a higher level of balance between the mechanical strength and storage stability of the mold than inorganic coated sand in which the amount of water of hydration of the metasilicate hydrate is not 6 or more and 8 or less.
[0024] The amount of water of hydration of the metasilicate hydrate can be adjusted by the method described below.
[0025] The amount of water of hydration of the metasilicate hydrate in the inorganic coated sand can be confirmed by the following method. [1] Measurement of moisture content (%) (A) in inorganic coated sand The moisture content (%)A in inorganic coated sand can be measured by either method 1 or 2 below. (Method 1) 10 g of inorganic coated sand to which additives such as amorphous SiO2-containing fine particles have not yet been added is weighed and placed in the pre-baked and weighed crucible, and the moisture content (%) in the inorganic coated sand (A) is calculated using the mass loss (%) after heating at 900°C for 1 hour. A = [(M1-M2) / M3] x 100 (M1: total mass (g) of the crucible and inorganic coated sand before firing, M2: total mass (g) of the crucible and inorganic coated sand after firing, M3: mass (g) of the inorganic coated sand before firing) (Method 2) The inorganic coated sand before adding additives such as amorphous SiO2-containing fine particles is measured under the following conditions using a simultaneous differential thermal and thermogravimetric analyzer (e.g., Thermo plus EVO2 TG-DTA8122 (manufactured by Rigaku Corporation)), and the weight loss (%) (A) at 200°C is calculated. <Measurement conditions> Measurement atmosphere: Air Sample amount: about 8mg Heating rate: 10.0℃ / min
[0026] [2] Measurement of solid content (%) of metasilicate hydrate (B) The percent solids of metasilicate hydrate in inorganic coated sand (B) can be measured by either Method 1 or Method 2 below. (Method 1) Weigh out 100 g of inorganic coated sand before adding additives such as amorphous SiO2-containing fine particles, immerse in 200 mL or more of water or hot water, and stir for 1 hour or more to extract metasilicate hydrate. Filter the resulting extract to remove the refractory aggregate, and then use a rotary evaporator to remove moisture by vacuum distillation at 40°C and an internal pressure of 15 mmHg or less. Then heat and dry at 120°C to 180°C for 1 to 3 hours, and weigh the dried material. Calculate the dry solid content (%) (B) of metasilicate hydrate in the inorganic coated sand. B = (M12 / M11) x 100 (M11: mass of inorganic coated sand (g), M12: dry weight (g)) (Method 2) Measurement is performed according to the following procedure <Preparation of extract> 30 g of inorganic coated sand before adding additives such as amorphous SiO2-containing fine particles is placed in a 200 ml tall beaker, 100 ml of pure water is added, and the mixture is stirred for 25 minutes with a magnetic stirrer to produce an extract. The supernatant of the extract is then filtered through a membrane filter (pore size: 0.45 μm), and 10 ml of the filtrate is placed in a 100 ml beaker. <Titration> 20 ml of 0.1 mol / l HCl aqueous solution was added to the 100 ml beaker containing 10 ml of the filtrate collected above, and then 0.1 mol / l NaOH aqueous solution was titrated using an automatic titrator (e.g., Eco Titrator (manufactured by Metrohm)) while stirring with a magnetic stirrer, and the titration amount X (ml) at which the pH reached 7 was measured using a pH meter. <Calculation of metasilicate solids> Acid consumption Y (mol) = ([Amount of HCl aqueous solution (ml)] - [Titer amount X (ml)]) / 1000 x [HCl aqueous solution concentration (mol / l)] = (20-X) / 1000 x 0.1 B = ([acid consumption Y (mol)] × 10 × [molecular weight of metasilicate anhydride] / [Na valence]) / (amount of inorganic coated sand (g)) × 100 = (Y × 10 × molecular weight of metasilicate anhydride / 2) / 30 × 100
[0027] [3] Calculation of the amount of water of hydration of metasilicate hydrate The water content (%) (A) in the obtained inorganic coated sand and the solid content (%) (B) of metasilicate hydrate are applied to the following formula to calculate the amount of water of hydration of the metasilicate hydrate. Amount of water of hydration of metasilicate hydrate = [(A) / molecular weight of water] / [(B) / molecular weight of metasilicate anhydride]
[0028] The inorganic coated sand is in a dry state. Dry coated sand means coated sand that can obtain a measured value when the dynamic angle of repose is measured regardless of the moisture content. The dynamic angle of repose is preferably 80° or less, more preferably 45° or less, and even more preferably 30° or less.
[0029] The dynamic angle of repose can be measured by the following method. (Method of measuring dynamic angle of repose) A cylindrical transparent plastic bottle is filled with half the volume of coated sand, and while holding it so that its axis is horizontal, it is rotated at a constant speed around the horizontal axis. The inclined surface of the coated sand layer flowing inside the cylinder becomes flat. The angle formed between this inclined surface and the horizontal plane is measured. Note that if the coated sand does not flow inside the cylinder, or if it does flow but the inclined surface of the coated sand layer does not form a flat surface, and as a result the dynamic angle of repose cannot be measured, it is in a wet state.
[0030] The inorganic coated sand is specifically composed of a group of inorganic coated sand particles, and the refractory aggregate is specifically composed of a group of refractory aggregate particles. From the viewpoint of improving the flowability and further improving the filling property into a molding die, the inorganic coated sand is preferably spherical. Here, spherical inorganic coated sand refers to sand having a round shape like a ball. More specifically, from the viewpoints of improving fluidity, mold quality, and mold strength, and of ease of mold making, the sphericity of the inorganic coated sand is preferably 0.75 or more, more preferably 0.80 or more, and even more preferably 0.82 or more. The upper limit of the sphericity is specifically 1 or less. In this embodiment, the sphericity of the inorganic coated sand specifically coincides with the sphericity of the refractory aggregate.
[0031] The sphericity of the inorganic coated sand is determined by analyzing the image (photograph) of the particle taken with an optical microscope or a digital scope (e.g., Keyence VH-8000) to determine the area of the projected cross section of the particle and the perimeter of the cross section, and then calculating the sphericity=[area of the projected cross section of the particle (mm 2 The particle diameter can be calculated by dividing the circumference (mm) of a perfect circle with the same area as the particle diameter by the circumference (mm) of the projected cross section of the particle, and then averaging the values obtained for any 50 particles.
[0032] The average particle size of the inorganic coated sand is preferably 0.05 mm or more, more preferably 0.1 mm or more, from the viewpoints of improving mold quality and mold strength, and of ease of mold making. In addition, when the average particle size of the inorganic coated sand is equal to or more than the above lower limit, the amount of coating layer used during mold production can be reduced, which is also preferable in that the inorganic coated sand can be easily regenerated. From the viewpoints of improving mold quality and strength, and of ease of mold making, the average particle size of the inorganic coated sand is preferably 2 mm or less, more preferably 1 mm or less, and even more preferably 0.5 mm or less. In addition, when the average particle size of the inorganic coated sand is equal to or less than the above upper limit, it is also preferable in that the porosity is reduced during mold production, and the mold strength can be increased.
[0033] In this embodiment, the average particle size of the inorganic coated sand and the refractory aggregate described later can be specifically measured by the following method.
[0034] (Method of measuring average particle size) If the sphericity of the particle from the projected cross section is 1, the diameter (mm) is measured, whereas if the sphericity is <1, the long axis diameter (mm) and short axis diameter (mm) of the randomly oriented particles are measured to calculate (long axis diameter + short axis diameter) / 2, and the average of the values obtained for any 100 particles is used as the average particle diameter (mm). The long axis diameter and short axis diameter are defined as follows: A particle is stabilized on a flat surface, and when the projected image of the particle on the flat surface is sandwiched between two parallel lines, the width of the particle at which the distance between the parallel lines is the smallest is called the short axis diameter, whereas the distance when the particle is sandwiched between two parallel lines perpendicular to the parallel lines is called the long axis diameter. The major axis diameter and minor axis diameter of a particle can be determined by taking an image (photograph) of the particle using an optical microscope or a digital scope (for example, VH-8000 model, manufactured by Keyence Corporation) and subjecting the obtained image to image analysis.
[0035] The inorganic coated sand may also have (iii) a fusion point of 40° C. or more and 60° C. or less, as determined in accordance with JACT Test Method C-1 Fusion Point Test Method for Inorganic Coated Sand. The fusion point of the inorganic coated sand may be 40° C. or higher, preferably 42° C. or higher, from the viewpoint of facilitating the molding of a complex shape, and may be 60° C. or lower, more preferably 58° C. or lower, even more preferably 55° C. or lower, and most preferably 50° C. or lower, from the viewpoint of improving mold strength. The fusion point (℃) of inorganic coated sand can be measured in accordance with JACT Test Method C-1 Fusion Point Test Method ("Test Method for Molds and Mold Materials", published in May 1999 by the Japan Small and Medium Enterprise Corporation, Information and Technology Department, Technical Support Division).
[0036] Each component of the inorganic coated sand will be described below.
[0037] [Fire-resistant aggregate] The fire-resistant aggregate according to this embodiment may be natural sand or artificial sand. Examples of natural sand include silica sand, which is mainly composed of quartz, chromite sand, zircon sand, olivine sand, and alumina sand. Examples of artificial sand include synthetic mullite sand, SiO2-based foundry sand mainly composed of SiO2, Al2O3-based foundry sand mainly composed of Al2O3, SiO2 / Al2O3-based foundry sand, SiO2 / MgO-based foundry sand, SiO2 / Al2O3 / ZrO2-based foundry sand, SiO2 / Al2O3 / Fe2O3-based foundry sand, slag-derived foundry sand, etc. Here, the main component refers to the component that is most abundant among the components contained in the sand. Artificial sand is not found in nature, but is found in sand that has been artificially prepared from metal oxide components and melted or sintered. In addition, recycled sand made from recycled refractory aggregate and recycled sand that has been regenerated can also be used. These may be used alone or in combination of two or more.
[0038] From the viewpoint of improving mold strength, the refractory aggregate according to this embodiment preferably contains one or more selected from the group consisting of SiO2 and Al2O3. From the viewpoint of improving mold strength, the refractory aggregate in this embodiment is preferably artificial sand, and among the artificial sands, at least one type selected from the group consisting of synthetic mullite sand, SiO2-based foundry sand, Al2O3-based foundry sand, SiO2 / Al2O3-based foundry sand, SiO2 / Al2O3 / ZrO2-based foundry sand, and SiO2 / Al2O3 / Fe2O3-based foundry sand is preferable.
[0039] The content of each component such as SiO2, Al2O3, Fe2O3, etc. in the refractory aggregate can be measured by a known analytical method, for example, fluorescent X-ray analysis, etc. Fluorescent X-ray can be analyzed by the following method. The refractory aggregate is adjusted to 0.1 μm or less using a vibration mill and heated at 1050°C for 1 hour. Then, 5 g of lithium tetraborate and 0.5 g of refractory aggregate are mixed and heated at 1200°C for 10 minutes to melt, and then cooled to prepare a glassy sample (glass bead method). The sample is subjected to X-ray fluorescence analysis using the Fundamental Parameter (FP) method using a ZSX Primus II X-ray fluorescence analyzer (Rigaku Corporation).
[0040] The degree of amorphization of the refractory aggregate is preferably 30% or more, more preferably 50% or more, even more preferably 65% or more, and even more preferably 80% or more, from the viewpoint of achieving a smoother surface of the aggregate and thus improved mold strength, and from the viewpoint of achieving low thermal expansion. The upper limit of the degree of amorphization of the refractory aggregate is not limited, but may be, for example, 100% or less, and may be 99% or less.
[0041] There are various methods for controlling the degree of amorphization of refractory aggregate, but it is generally preferable to use a manufacturing method that rapidly cools the molten material. For example, there is a method in which the raw material is melted and rapidly cooled by crushing it with air, or a method in which it is treated in a flame and rapidly cooled. In either case, the cooling method may be appropriately selected at various speeds depending on the material and particle size. In addition, a method in which a crystallized material is once made amorphic by heat treatment and cooling treatment may also be considered.
[0042] The degree of amorphization of the refractory aggregate can be determined by the X-ray diffraction method described below. (X-ray diffraction method) The refractory aggregate is crushed in a mortar and pressed against an X-ray glass holder of a powder X-ray diffractometer for measurement. The powder X-ray diffractometer is a Rigaku MultiFlex (CuKα light source, tube voltage 40 kV, tube current 40 mA), and the measurement is performed in the range of 2θ = 5 to 90° with a scan interval of 0.01°, a scan speed of 2° / min, and slits DS1, SS1, and RS0.3 mm. In the range of 2θ = 10° to 50°, the X-ray intensities on the low angle side and the high angle side are connected with a straight line, the area under the straight line is taken as the background, the crystallinity is calculated using the software attached to the device, and the degree of amorphousness is calculated by subtracting it from 100. Specifically, for the area above the background, the amorphous peak (halo) and each crystalline component are separated by curve fitting, the area of each is calculated, and the degree of amorphousness (%) is calculated using the following formula. Amorphous ratio (%) = (area of halo) / (area of crystalline component + area of halo) x 100
[0043] The refractory aggregate is preferably spherical from the viewpoint of improving the fluidity of the inorganic coated sand and further improving the fillability into a mold. The preferred range of sphericity of the refractory aggregate is the same as that of the inorganic coated sand. The sphericity of the refractory aggregate can be measured in the same manner as the sphericity of the inorganic coated sand.
[0044] The preferred range of the average particle size of the refractory aggregate is the same as that of the inorganic coated sand. The average particle size of the refractory aggregate can be measured in the same manner as the average particle size of the inorganic coated sand.
[0045] [Inorganic binder layer] The inorganic binder layer is formed on the surface of the refractory aggregate, and serves as a coating layer that covers the surface of the refractory aggregate. However, the term "covering the surface" does not necessarily mean that the layer is continuous, and may include discontinuous regions.
[0046] The inorganic binder layer contains an inorganic binder and is composed of metasilicate hydrate and amorphous SiO2-containing fine particles as essential components. Specifically, for example, the inorganic binder layer can be a layer in which metasilicate hydrate and amorphous SiO2-containing fine particles are mixed and coated; a layer in which amorphous SiO2-containing fine particles are further coated on a layer coated with metasilicate hydrate; or a layer in which amorphous SiO2-containing fine particles are further coated on a layer in which metasilicate hydrate and amorphous silica are mixed and coated.
[0047] From the viewpoint of obtaining a high-strength casting mold, the coating amount of the inorganic binder layer contained in the inorganic coated sand is, for example, 0.1 parts by mass or more relative to 100 parts by mass of the refractory aggregate, preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more. In addition, the coating amount of the inorganic binder layer contained in the inorganic coated sand is, for example, 15 parts by mass or less, preferably 10 parts by mass or less, and more preferably 8 parts by mass or less, relative to 100 parts by mass of the refractory aggregate, from the viewpoint of obtaining a high-strength casting mold.
[0048] The water content (including water of crystallization) in the inorganic binder layer contained in the inorganic coated sand is preferably 75 parts by mass or more, more preferably 80 parts by mass or more, and even more preferably 85 parts by mass or more, per 100 parts by mass of metasilicate (anhydrous equivalent), from the viewpoints of obtaining a high-strength casting mold and of easily producing the mold, and is preferably 130 parts by mass or less, more preferably 125 parts by mass or less, and even more preferably 120 parts by mass or less, from the viewpoints of improving the fluidity and further improving the fillability into the mold.
[0049] Hereinafter, components constituting the inorganic binder layer of the present embodiment will be described.
[0050] (Inorganic binder) The inorganic binder has a function of firmly binding the mold sands together so that a desired mold can be obtained when the mold is made using the inorganic coated sand. The inorganic binder is also one component constituting the inorganic binder layer. The inorganic binder includes, for example, a water-soluble silicic acid compound, and preferably includes at least one selected from sodium silicate and sodium metasilicate. The inorganic binder may further include a binder mainly composed of a water-soluble silicic acid compound other than the above. Specific examples of silicic acid compounds other than sodium silicate and sodium metasilicate include potassium silicate, potassium metasilicate, lithium silicate, and ammonium silicate.
[0051] The inorganic binder has a melt viscosity at 80° C. of 32 mPa·s or more, and preferably 35 mPa·s or more, from the viewpoint of improving the mechanical strength of the mold. On the other hand, the melt viscosity of the inorganic binder at 80°C is 150 mPa·s or less, and preferably 120 mPa·s or less, from the viewpoint of improving the storage stability of the inorganic coated sand while maintaining good mechanical strength of the mold.
[0052] The melt viscosity of the inorganic binder at 80°C was measured using a rheometer with a parallel plate (PP60) as the jig, set at 80°C and at a shear rate of 100 s ―1 It can be carried out under the conditions.
[0053] (Metasilicate hydrate) The metasilicate hydrate is one of the components constituting the inorganic binder layer, and is also one of the components constituting the inorganic binder. The use of the metasilicate hydrate is preferable because it can improve the crystallinity of the inorganic binder layer, and furthermore, the inorganic coated sand becomes a dry state and has excellent fluidity at room temperature. In addition, the use of the metasilicate hydrate allows the inorganic binder layer to be formed on the surface of the refractory aggregate without being dissolved in water. That is, in the process of producing the inorganic coated sand, more specifically, in the process of mixing the refractory aggregate and the inorganic binder, it is not necessary to use an aqueous solution of the metasilicate hydrate, so the process of removing water can be omitted, and the production method can be simplified. In addition, since the metasilicate of the inorganic binder layer is a hydrate, it is not necessary to ventilate water vapor to harden the mold, and the equipment can be simplified. In addition, metasilicate hydrate can also be produced using a mixed liquid obtained by mixing metasilicate hydrate crystals, water glass, caustic alkali, and water in a specific ratio, a mixed liquid obtained by mixing metasilicate anhydrous and water in a specific ratio, a mixed liquid obtained by mixing metasilicate pentahydrate and water in a specific ratio, or a metasilicate melt obtained by volatilizing a specific amount of water from a melt of metasilicate nonahydrate. These raw materials can also be added separately to refractory aggregate to form a metasilicate hydrate composition on the surface of the refractory aggregate. In the present embodiment, the metasilicate refers to a compound having a SiO2 / Na2O molar ratio of 0.9 to 1.1 among silicates.
[0054] Specific examples of water glass include one or more types selected from the group consisting of sodium silicate No. 1 to No. 5. Sodium silicate is classified into No. 1 to No. 5 based on the molar ratio of SiO2 / Na2O, and sodium silicate No. 1 to No. 3 are also specified in the group standard (implementation date: March 1, 2022) created by the Sodium Silicate Committee of the Japan Inorganic Chemicals Association. The molar ratio of SiO2 / Na2O for each type is specifically as follows: Sodium silicate No. 1: SiO2 / Na2O molar ratio = 2.0-2.3 Sodium silicate No. 2: SiO2 / Na2O molar ratio = 2.4-2.6 Sodium silicate No. 3: SiO2 / Na2O molar ratio = 2.8-3.3 Sodium silicate No. 4: SiO2 / Na2O molar ratio = 3.3-3.5 Sodium silicate No. 5: SiO2 / Na2O molar ratio = 3.6-3.8 Moreover, two or more kinds of sodium silicate may be mixed to adjust the molar ratio of SiO2 / Na2O to a desired level. The water glass is preferably at least one selected from sodium silicate No. 1 and sodium silicate No. 2.
[0055] In this embodiment, the amount of water of hydration of the metasilicate hydrate is 6 or more and 8 or less. By setting it in this numerical range, it is possible to obtain good storage stability of the inorganic coated sand while improving the mechanical strength of the mold using it. Furthermore, by setting the amount of water of hydration of the metasilicate hydrate to be equal to or more than the above lower limit, it is possible to improve the mechanical strength of the mold while maintaining good storage stability. On the other hand, by setting the amount of water of hydration of the metasilicate hydrate to be equal to or less than the above upper limit, it is possible to improve the storage stability while maintaining good mechanical strength of the mold.
[0056] The salt of metasilicate hydrate is preferably an alkali metal, more preferably one or more selected from lithium, sodium, and potassium, more preferably at least one of sodium and potassium, and even more preferably sodium.
[0057] The content of metasilicate hydrate in the inorganic binder layer is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on the entire inorganic binder layer, from the viewpoint of improving the strength of the mold and improving the surface shape of the mold. Also, from the viewpoint of improving the surface shape of the mold, the content of metasilicate hydrate in the inorganic binder layer is preferably 95% by mass or less, more preferably 90% by mass or less, based on the entire inorganic binder layer.
[0058] The content of metasilicate (anhydride equivalent) in the inorganic binder is preferably 11% by mass or more, more preferably 45% by mass or more, from the viewpoint of improving the storage stability of the inorganic coated sand, while it is preferably 56% by mass or less, more preferably 48% by mass or less, from the viewpoint of improving the mold strength.
[0059] In addition, from the viewpoint of improving the mold strength and improving the surface shape of the mold, the content of metasilicate hydrate in the inorganic coated sand is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.5 parts by mass or more, still more preferably 0.8 parts by mass or more, and especially preferably 1 part by mass or more, per 100 parts by mass of the refractory aggregate. In addition, from the viewpoint of improving the filling property into the molding die, the content of metasilicate hydrate in the inorganic coated sand is preferably 9 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 4 parts by mass or less, per 100 parts by mass of the refractory aggregate.
[0060] (Amorphous SiO2-containing fine particles) Amorphous SiO2-containing microparticles are used because of their high reactivity with metasilicate hydrate. This makes it easier to improve mechanical strength. Examples of amorphous SiO2-containing microparticles include precipitated silica, calcined silica produced in an electric arc or by flame hydrolysis, silica produced by thermal decomposition of ZrSiO4, silica produced during the manufacture of Fe-Si, silica produced by oxidation of metal silicon with an oxygen-containing gas, and spherical particles of quartz glass powder produced from crystalline quartz by melting and subsequent quenching. These can be used alone, or two or more of them can be mixed together.
[0061] The degree of amorphization of the amorphous SiO2-containing fine particles is preferably 80% or more, more preferably 90% or more, even more preferably 93% or more, even more preferably 95% or more, and especially preferably 98% or more, from the viewpoint of more firmly binding the particles of the inorganic coated sand via the amorphous SiO2-containing fine particles. The upper limit of the degree of amorphization of the amorphous SiO2-containing fine particles is not limited, but may be, for example, 100% or less, 99.8% or less, or 99% or less.
[0062] The degree of amorphization of the amorphous SiO2-containing fine particles can be determined by the X-ray diffraction method similar to that for the refractory aggregate.
[0063] The amorphous SiO2-containing fine particles are preferably in the form of particles. The average particle size of the amorphous SiO2-containing microparticles is preferably 0.1 μm or more, more preferably 0.3 μm or more, from the viewpoint of improving mold strength per unit mass and improving handling. Also, from the viewpoint of improving mold strength per unit mass, the average particle size of the amorphous SiO2-containing microparticles is preferably 2.0 μm or less, more preferably 1.0 μm or less, even more preferably 0.8 μm or less, and even more preferably 0.6 μm or less. Here, the average particle size of the amorphous SiO2-containing microparticles is obtained from the image observed by a scanning electron microscope, and various image analysis methods can be used for this purpose. Irregular particle selection may be performed as a pretreatment. For example, after determining the amorphous SiO2-containing microparticles based on the elements, 100 amorphous SiO2-containing microparticles are arbitrarily selected, their particle sizes are measured, and the average value of the particle sizes of 80 amorphous SiO2-containing microparticles, which are excluding the 10 particles counted from the maximum particle size and the 10 particles counted from the minimum particle size, totaling 20 amorphous SiO2-containing microparticles, can be used as the average particle size of the amorphous SiO2-containing microparticles.
[0064] From the viewpoint of improving mold strength, the SiO2 mass% in the amorphous SiO2-containing fine particles is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, even more preferably 85 mass% or more, and even more preferably 90 mass% or more. The SiO2 mass% in the amorphous SiO2-containing fine particles can be measured by X-ray fluorescence method in the same manner as the refractory aggregate.
[0065] The content of the amorphous SiO2-containing microparticles is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of the fire-resistant aggregate, from the viewpoints of improving the mold strength and improving the mold surface shape while obtaining storage stability, and suppressing dust scattering. In addition, the content of the amorphous SiO2-containing microparticles is preferably 25 parts by mass or more, more preferably 30 parts by mass or more, and preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 145 parts by mass or less, per 100 parts by mass of metasilicate (anhydrous equivalent).
[0066] (others) The inorganic binder layer may contain, as components other than the metasilicate hydrate and the amorphous SiO2-containing fine particles, inorganic particles other than the amorphous SiO2-containing fine particles, and other additives such as coupling agents, lubricants, and release agents.
[0067] Examples of inorganic particles other than the amorphous SiO2-containing fine particles include, but are not limited to, carbonates such as crystalline silica, silicon, zinc carbonate, basic zinc carbonate, iron carbonate, manganese carbonate, copper carbonate, aluminum carbonate, barium carbonate, magnesium carbonate, calcium carbonate, lithium carbonate, potassium carbonate, and sodium carbonate; borates such as sodium tetraborate, potassium tetraborate, lithium tetraborate, ammonium tetraborate, calcium tetraborate, strontium tetraborate, silver tetraborate, sodium metaborate, potassium metaborate, lithium metaborate, ammonium metaborate, calcium metaborate, silver metaborate, copper metaborate, lead metaborate, and magnesium metaborate; sodium sulfate, potassium sulfate, lithium metaborate, ammonium metaborate, calcium metaborate, silver metaborate, copper metaborate, lead metaborate, and magnesium metaborate; Examples of suitable oxides include sulfates such as lithium, lithium sulfate, magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate, titanium sulfate, aluminum sulfate, zinc sulfate, and copper sulfate; phosphates such as sodium phosphate, sodium hydrogen phosphate, potassium phosphate, potassium hydrogen phosphate, lithium phosphate, lithium hydrogen phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, aluminum phosphate, and zinc phosphate; hydroxides such as lithium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, aluminum hydroxide, and zinc hydroxide; and oxides such as silicon, zinc, magnesium, aluminum, calcium, lithium, copper, iron, boron, and zirconium.
[0068] The coupling agent is not limited, but examples thereof include silane coupling agents, zircon coupling agents, and titanium coupling agents. Examples of lubricants include, but are not limited to, waxes such as paraffin wax, synthetic polyethylene wax, and montanic acid wax; fatty acid amides such as stearic acid amide, oleic acid amide, and erucic acid amide; alkylene fatty acid amides such as methylene bis-stearic acid amide and ethylene bis-stearic acid amide; stearic acid; stearyl alcohol; metal stearates such as lead stearate, zinc stearate, calcium stearate, and magnesium stearate; stearic acid monoglyceride; stearyl stearate; and hydrogenated oils. Examples of the release agent include, but are not limited to, paraffin, wax, light oil, machine oil, spindle oil, insulating oil, waste oil, vegetable oil, fatty acid ester, organic acid, graphite particles, mica, vermiculite, fluorine-based release agents, and silicone-based release agents.
[0069] <Manufacturing method of inorganic coated sand> Next, a method for producing the inorganic coated sand will be described. The method for producing inorganic coated sand of the present embodiment is a method for producing dry inorganic coated sand having refractory aggregate and an inorganic binder layer covering the surface of the refractory aggregate, wherein the inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, and satisfies at least one of the following (i) to (iii): (i) the inorganic binder constituting the inorganic binder layer has a melt viscosity at 80°C of 32 mPa s or more and 150 mPa s or less; (ii) the amount of water of hydration of the metasilicate hydrate is 6 or more and 8 or less; (iii) The fusion point of the inorganic coated sand, as determined in accordance with JACT Test Method C-1 Fusion Point Test Method, is 40°C or higher and 60°C or lower.
[0070] First, an example of a method for producing the inorganic coated sand of this embodiment is a production method including the following steps (1) and (2). Step (1): A step of mixing a refractory aggregate, metasilicate nonahydrate, and metasilicate pentahydrate to obtain a mixture. Step (2): Cooling the mixture
[0071] Step (1) is carried out at a temperature equal to or higher than the melting point of the mixture of metasilicate nonahydrate and metasilicate pentahydrate used, which can be obtained by mixing metasilicate nonahydrate and metasilicate pentahydrate in any ratio. By mixing the refractory aggregate, metasilicate nonahydrate, and metasilicate pentahydrate at a temperature equal to or higher than the melting point of the mixture, an inorganic binder having a melt viscosity of 32 to 150 mPa s at 80°C is obtained, and inorganic coated sand having a metasilicate hydrate with an amount of water of hydration of 6 or more and 8 or less is obtained. Furthermore, for example, by mixing metasilicate nonahydrate and metasilicate pentahydrate in a molar ratio of 75:25 and appropriately adjusting the mixing procedure and conditions, the amount of water of hydration of the metasilicate hydrate can be controlled to be 8.
[0072] In addition, examples of a method for mixing the refractory aggregate with metasilicate nonahydrate and metasilicate pentahydrate at a temperature equal to or higher than the melting point of a mixture of metasilicate nonahydrate and metasilicate pentahydrate include a method in which metasilicate nonahydrate and metasilicate pentahydrate are added to the refractory aggregate heated to a temperature equal to or higher than the melting point of the mixture, and the refractory aggregate and metasilicate hydrate are mixed while melting the metasilicate hydrate (step (1A)), and a method in which a mixture of metasilicate nonahydrate and metasilicate pentahydrate that has been heated and melted is added to the refractory aggregate and mixed (step (1B)). Further examples include a method (step (1C)) in which refractory aggregate heated to a temperature equal to or higher than the melting point of a mixture of metasilicate nonahydrate and metasilicate pentahydrate is added to the mixture, and the refractory aggregate and metasilicate hydrate are mixed while melting the metasilicate hydrate, and a method (step (1D)) in which refractory aggregate is added to a mixture of metasilicate nonahydrate and metasilicate pentahydrate that has been heated and melted to a temperature equal to or higher than the melting point of the mixture, and mixed. Among these, the step (1B) is preferred from the viewpoint of shortening the time required for covering the surface of the refractory aggregate with the fluidized metasilicate hydrate.
[0073] From the same viewpoint, it is preferable that in step (1), metasilicate nonahydrate and metasilicate pentahydrate are mixed without being previously dissolved in an aqueous solution, and it is also preferable that step (1) does not include a step of intentionally adding water. The mixing conditions such as the stirring speed and processing time when mixing the refractory aggregate with the metasilicate nonahydrate and metasilicate pentahydrate can be appropriately determined depending on the processing amount of the mixture.
[0074] In step (2), the mixture obtained in step (1) is cooled to a temperature below the melting point of the mixture to reduce the fluidity of the metasilicate hydrate and fix the metasilicate hydrate to the surface of the refractory aggregate, thereby forming a metasilicate hydrate layer, i.e., an inorganic binder layer. In this way, the inorganic coated sand according to this embodiment can be obtained.
[0075] Next, another example of the method for producing the inorganic coated sand of this embodiment includes a production method including the following step (3). Step (3): Mixing the refractory aggregate with a solution containing water glass, caustic alkali, and water to obtain a mixture containing metasilicate hydrate.
[0076] In step (3), the molten liquid of metasilicate hydrate of this embodiment can be prepared by adjusting the mole ratio of SiO2:M2O (M is an alkali metal):H2O molecules in the mixture of water glass, caustic alkali, and water to 1:1:6 to 8. This makes it possible to obtain an inorganic binder having a melt viscosity at 80°C of 32 mPa s or more and 150 mPa s or less, and to obtain inorganic coated sand in which the amount of water of hydration of the metasilicate hydrate is 6 or more and 8 or less. The water glass serves as an inorganic binder constituting the inorganic binder layer. Examples of caustic alkali include caustic soda (sodium hydroxide; NaOH) and caustic potash (potassium hydroxide; KOH). The conditions for mixing the water glass, the caustic alkali, and the water are not particularly limited, and a known method can be used. For example, the mixing may be performed at ambient temperature, and if the molten liquid generates heat, the mixing may be continued and then allowed to stand until the temperature reaches the ambient temperature.
[0077] In addition, examples of the method for mixing the refractory aggregate with the solution containing water glass, caustic alkali, and water include a method in which the solution is poured into the refractory aggregate and mixed (step (3A)), and a method in which the refractory aggregate is poured into the solution and mixed (step (3B)).
[0078] In this way, the inorganic coated sand according to this embodiment can be obtained.
[0079] [Casting mold] Next, the casting mold according to this embodiment will be described. The casting mold according to this embodiment is formed from inorganic coated sand. The method for producing a casting mold includes the following steps (4) and (5). Step (4): Filling the inorganic coated sand into a mold to give the desired casting shape. Step (5): A step of heating the mold filled with the inorganic coated sand to harden the inorganic coated sand.
[0080] In step (4), from the viewpoint of improving mold productivity, the mold is preferably preheated to keep it warm. From the viewpoint of improving mold productivity and mold strength, the heating temperature is preferably 100° C. or higher, more preferably 150° C. or higher, and is preferably 300° C. or lower, more preferably 250° C. or lower.
[0081] In step (5), the mold filled with the inorganic coated sand is heated without passing water vapor through it. By using the inorganic coated sand of this embodiment, the inorganic coated sand can be hardened without passing water vapor through it, and equipment for passing water vapor through it is not necessary. From the viewpoint of improving mold productivity and from the viewpoint of improving mold strength, the heating temperature is preferably 100° C. or higher, more preferably 150° C. or higher, and also preferably 300° C. or lower, more preferably 250° C. or lower. From the viewpoint of obtaining stable mold strength, the heating time is preferably 30 seconds or higher, more preferably 60 seconds or higher, and also preferably 600 seconds or lower.
[0082] The inorganic coated sand according to this embodiment can be used alone or in combination with other known refractory aggregates and other additives to form a desired casting mold.
[0083] <Inorganic coated sand composition> The inorganic coated sand composition of the present embodiment is a mixture of the above-mentioned inorganic coated sand with refractory aggregate, inorganic particles, a coupling agent, a lubricant, a mold release agent, etc. It is also possible to manufacture a casting mold using the inorganic coated sand composition in the same manner as the above-mentioned inorganic coated sand. The content of the inorganic coated sand in the total amount of the inorganic coated sand composition is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, in order to obtain good strength and other properties due to the inorganic coated sand. The refractory aggregate, inorganic particles, coupling agents, lubricants, release agents, etc. used in the inorganic coated sand composition are the same as those used in the inorganic coated sand described above.
[0084] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above may also be adopted. Furthermore, modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention.
[0085] In relation to the above-mentioned embodiments, the present invention further discloses the following inorganic coated sand, a method for manufacturing the inorganic coated sand, and a method for manufacturing a casting mold.
[0086] <1> A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic coated sand, wherein the inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, and the melt viscosity of the inorganic binder constituting the inorganic binder layer at 80°C is 32 mPa·s or more and 150 mPa·s or less. <2> A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic coated sand, wherein the inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, and the amount of water of hydration of the metasilicate hydrate is 6 or more and 8 or less. <3> A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic binder layer contains metasilicate hydrate and amorphous SiO2-containing fine particles, Inorganic coated sand with a fusion point of 40°C or higher and 60°C or lower, according to JACT test method C-1 fusion point test method. <4> <1> ~ <3> The inorganic coated sand according to any one of the above, The inorganic coated sand, wherein the metasilicate hydrate has an amount of water of hydration of 6 or more and 8 or less. <5> <1> ~ <4> The inorganic coated sand according to any one of the above, The inorganic coated sand has an inorganic binder layer contained therein in an amount of 0.1 parts by mass or more, preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, still more preferably 2 parts by mass or more, and is 15 parts by mass or less, preferably 10 parts by mass or less, more preferably 8 parts by mass or less, relative to 100 parts by mass of the fire-resistant aggregate. <6> <1> ~ <5> The inorganic coated sand according to any one of the above, The content of amorphous SiO2-containing fine particles is 0.1 parts by mass or more, preferably 0.2 parts by mass or more, and 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, per 100 parts by mass of the refractory aggregate. <7> <1> ~ <6> The inorganic coated sand according to any one of the above, The inorganic coated sand has a dynamic angle of repose of preferably 80° or less, more preferably 45° or less, and further preferably 30° or less. <8> <1> ~ <7> The inorganic coated sand according to any one of the above, The degree of amorphization of the refractory aggregate is preferably 30% or more, more preferably 50% or more, even more preferably 65% or more, and even more preferably 80% or more, while it is preferably 100% or less, and more preferably 99% or less. <9> <1> ~ <8> The inorganic coated sand according to any one of the above, An inorganic coated sand, wherein the sphericity of the refractory aggregate is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, still more preferably 0.95 or more, and still more preferably 0.97 or more. <10> <1> ~ <9> The inorganic coated sand according to any one of the above, The average particle size of the refractory aggregate is preferably 0.05 mm or more, more preferably 0.1 mm or more, and is preferably 2 mm or less, more preferably 1 mm or less, and even more preferably 0.5 mm or less. <11> <1> ~ <10> The inorganic coated sand according to any one of the above, The water content (including water of crystallization) in the inorganic binder layer contained in the inorganic coated sand is preferably 75 parts by mass or more, more preferably 80 parts by mass or more, and even more preferably 85 parts by mass or more, relative to 100 parts by mass of metasilicate (anhydrous equivalent), and is preferably 130 parts by mass or less, more preferably 125 parts by mass or less, and even more preferably 120 parts by mass or less. <12> <1> ~ <11> The inorganic coated sand according to any one of the above, The content of metasilicate hydrate in the inorganic binder layer is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, and particularly preferably 40% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, based on the entire inorganic binder layer. <13> <1> ~ <12> The inorganic coated sand according to any one of the above, The inorganic coated sand has a metasilicate content (anhydrous equivalent) of preferably 11% by mass or more, more preferably 45% by mass or more, and also preferably 56% by mass or less, more preferably 48% by mass or less. <14> <1> ~ <13> The inorganic coated sand according to any one of the above, The content of metasilicate hydrate in the inorganic coated sand is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.5 parts by mass or more, even more preferably 0.8 parts by mass or more, particularly preferably 1 part by mass or more, and is preferably 9 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 4 parts by mass or less, per 100 parts by mass of refractory aggregate. <15> <1> ~ <14> The inorganic coated sand according to any one of the above, The degree of amorphization of the amorphous SiO2-containing microparticles is preferably 80% or more, more preferably 90% or more, even more preferably 93% or more, even more preferably 95% or more, and especially preferably 98% or more, and is 100% or less, in the inorganic coated sand. <16> <1> ~ <15> The inorganic coated sand according to any one of the above, The average particle size of the amorphous SiO2-containing microparticles is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 2.0 μm or less, more preferably 1.0 μm or less, even more preferably 0.8 μm or less, and even more preferably 0.6 μm or less. <17> <1> ~ <16> 2. A casting mold using the inorganic coated sand according to claim 1. <18> <1> ~ <16> 10. An inorganic coated sand composition comprising the inorganic coated sand according to claim 9. <19> <18> The inorganic coated sand composition according to claim 1, wherein the content of the inorganic coated sand relative to the total amount of the inorganic coated sand composition is preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more. <20> <18> or <19> A casting mold using the inorganic coated sand composition according to claim 1. <21> <1> ~ <16> A method for producing the inorganic coated sand according to any one of the above, (1) mixing the refractory aggregate, metasilicate nonahydrate, and metasilicate pentahydrate to obtain a mixture; (2) cooling the mixture; Including, The step (1) includes mixing the metasilicate nonahydrate and the metasilicate pentahydrate at a temperature equal to or higher than the melting point of the mixture, The step (2) comprises cooling the mixture of the metasilicate nonahydrate and the metasilicate pentahydrate to a temperature lower than the melting point of the mixture. <22> <1> ~ <16> A method for producing the inorganic coated sand according to any one of the above, A method for producing inorganic coated sand, comprising the step (3) of mixing the refractory aggregate with a solution containing water glass, caustic alkali, and water to obtain a mixture containing metasilicate hydrate. EXAMPLES
[0087] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0088] (1) Material The materials used in the following examples and comparative examples will be described.
[0089] [Fire-resistant aggregate] ·Refractory aggregate 1: Mikawa silica sand R6 (manufactured by Mikawa Silica Co., Ltd., average particle size: 200 μm, amorphousness 0.2%, sphericity 0.85) Fire-resistant aggregate 2: Espearl #60L (manufactured by Yamakawa Sangyo Co., Ltd., average particle size: 241 μm, amorphous degree 45%, sphericity 0.97)
[0090] [Metasilicate hydrate (inorganic binder)] Metasilicate 1: Sodium metasilicate nonahydrate (Na2SiO3·9H2O) manufactured by Nippon Chemical Industry Co., Ltd., melting point 47°C Metasilicate 2: Sodium metasilicate pentahydrate (Na2SiO3·5H2O) manufactured by Nippon Chemical Industry Co., Ltd., melting point 72°C Metasilicate 3: Sodium metasilicate anhydrous manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Metasilicates 4 to 6: Each water glass-containing aqueous solution prepared by the following procedure
[0091] (procedure) Water glass, caustic soda (NaOH), and water were mixed in a mixer for 10 minutes in the ratios (parts by mass) shown in Table 1 below to obtain metasilicates 4 to 6 having the amounts of water of hydration shown in Table 1, respectively.
[0092] [Table 1]
[0093] No. 1 50 water glass: Fuji Chemical Co., Ltd., SiO2 (%) = 30.0, Na2O (%) = 14.7, solid content 44.7% by mass No. 1 59 Water Glass: Fuji Chemical Co., Ltd., SiO2 (%) = 36.2, Na2O (%) = 18.2, solid content 54.4% by mass NaOH: Caustic soda, Fujifilm Wako Pure Chemical NaOH, granular
[0094] [Amorphous SiO2-containing particles] Amorphous SiO2-containing microparticles 1: Denka fused silica SFP-20M manufactured by Denka Corporation (average particle size: 0.4 μm, degree of amorphousness 99.5% or more, SiO2 mass%: 99% or more) Amorphous SiO2-containing fine particles 2: Tomoe Engineering silica fume EFACO (average particle size: 0.3 μm, degree of amorphization 95% or more, SiO2 mass%: 92.4% by mass)
[0095] (2) Preparation of inorganic coated sand <Examples 1, 3-4, 6-8, Comparative Examples 1-6> The refractory aggregate 1 (100 parts by mass) was put into the mixer. Next, the mixture of metasilicate 1 and metasilicate 2 in the amount (parts by mass) shown in Table 2 was heated to 80 ° C. to melt and obtain a molten liquid. Next, the molten liquid was put into the mixer and uniformly kneaded with the refractory aggregate 1. While continuing the stirring, the mixture of metasilicate 1 and metasilicate 2 was naturally cooled to below the melting point, and the stirring was stopped 7 minutes after the start of the kneading, and dry sand having room temperature fluidity was obtained. The hydrate amount shown in Table 2 was measured using this dry sand by the hydrate amount measurement method described later. Then, the amorphous SiO2-containing fine particles in the amount (parts by mass) shown in Table 2 were further put in and kneaded for 2 minutes. Table 2 shows the blending composition of the obtained inorganic coated sand. The melting points of the mixtures of metasilicate 1 and metasilicate 2 were all lower than 80°C, and were in the range of 48 to 63°C when the amount of water of hydration was 8 to 6.
[0096] <Example 2> The inorganic coated sand shown in Table 2 was obtained in the same manner as in Example 1, except that the mixture of metasilicate 3 and water and amorphous SiO2-containing microparticles in the amounts (parts by mass) shown in Table 2 were added to the fire-resistant aggregate 1 (100 parts by mass).
[0097] <Example 5> The inorganic coated sand shown in Table 2 was obtained in the same manner as in Example 1, except that the mixture of metasilicate 2 and water and amorphous SiO2-containing microparticles in the amounts (parts by mass) shown in Table 2 were added to the fire-resistant aggregate 1 (100 parts by mass).
[0098] <Examples 9 to 11> The inorganic coated sand shown in Table 2 was obtained in the same manner as in Example 1, except that any one of metasilicates 4 to 6 and amorphous SiO2-containing microparticles were added to the fire-resistant aggregate 1 (100 parts by mass) in the amounts (parts by mass) shown in Table 2.
[0099] <Examples 12 to 15 and Comparative Examples 7 to 8> The inorganic coated sand shown in Table 2 was obtained in the same manner as in Example 1, except that metasilicate 1, metasilicate 2, and amorphous SiO2-containing microparticles were added to refractory aggregate 2 (100 parts by mass) in the amounts (parts by mass) shown in Table 2.
[0100] <Examples 16 to 18> The inorganic coated sand shown in Table 2 was obtained in the same manner as in Example 1, except that any one of metasilicates 4 to 6 and amorphous SiO2-containing microparticles were added to the fire-resistant aggregate 2 (100 parts by mass) in the amounts (parts by mass) shown in Table 2.
[0101] (3) Evaluation and measurement The following evaluations and measurements were carried out for each metasilicate hydrate (inorganic binder) or each inorganic coated sand.
[0102] <Measurement of the amount of water of hydration> (1) 10 g of inorganic coated sand, to which additives such as amorphous SiO2-containing fine particles had not yet been added, was weighed and placed in a pre-baked and weighed crucible. The moisture content (%) in the inorganic coated sand (A) was calculated from the mass loss (%) after heating at 900°C for 1 hour. A = [(M1-M2) / M3] x 100 (M1: total mass (g) of the crucible and inorganic coated sand before firing, M2: total mass (g) of the crucible and inorganic coated sand after firing, M3: mass (g) of the inorganic coated sand before firing) (2) 100 g of inorganic coated sand before adding additives such as amorphous SiO2-containing fine particles was weighed, immersed in 200 mL or more of hot water and stirred for 1 hour or more to extract metasilicate hydrate. The refractory aggregate was removed from the obtained extract by filtration, and the water was removed by vacuum distillation using a rotary evaporator at 40°C and an internal pressure of 15 mmHg or less. The sand was then dried by heating at 180°C for 3 hours, and the weight of the dried material was weighed. The dry solid content (%) (B) of metasilicate hydrate in the inorganic coated sand was calculated. B = (M12 / M11) x 100 (M11: mass of inorganic coated sand (g), M12: dry weight (g)) (3) The moisture content (%) (A) in the obtained inorganic coated sand and the dry solid content (%) (B) of metasilicate hydrate were applied to the following formula to calculate the amount of water of hydration of the metasilicate hydrate. Amount of water of hydration of metasilicate hydrate = [(A) / molecular weight of water] / [(B) / molecular weight of metasilicate anhydride]
[0103] <Melt viscosity measurement of inorganic binder> Each metasilicate hydrate heated to 80°C was rheometered at 80°C with a parallel plate (PP60) in a Thermo Scientific MARS40 rheometer at a shear rate of 100 s ―1 The viscosity of each of the compositions was measured. The evaluation results are shown in Table 2.
[0104] <Fusion point measurement> The fusion point (℃) of inorganic coated sand was measured in accordance with JACT Test Method C-1 Fusion Point Test Method ("Test Method for Molds and Mold Materials", published in May 1999 by the Japan Small and Medium Enterprise Corporation, Information and Technology Department, Technical Support Division). However, taking into consideration the characteristics of inorganic coated sand, the measurement method was changed as follows. Two hot plates (Type 1900 Hot Plate, manufactured by Barnstead) were placed at an interval of about 18 cm, and a rectangular metal rod (made of SUS) with a width of 1.5 cm, length of 22 cm, and thickness of 0.5 cm was placed on the hot plate so that each end was about 2 cm above the hot plate. Then, only one of the hot plates was heated with a memory of 200°C. After about 30 minutes, the temperature of the metal rod on the heated hot plate was measured with a contact thermometer (MC1000, manufactured by Chino Co.) and confirmed to be 100°C or higher, and similarly, the temperature of the metal rod on the unheated hot plate was confirmed to be about 25°C. Then, inorganic coated sand was quickly sprinkled on the metal rod, and after 60 seconds, the metal rod was rotated 180° around its long axis so that the inorganic coated sand-sprinkled surface was facing downward. The temperature of the hottest part at the boundary between the part with and without inorganic coated sand was measured with a contact thermometer. This procedure was repeated three times, and the average of the measured temperatures was taken as the fusion point of the inorganic coated sand. The measurement results are shown in Table 2.
[0105] <Mold strength> Using each inorganic coated sand, a mold was made according to the following procedure, and the mold strength was measured. The evaluation results are shown in Table 2. (procedure) A mold for 22.3 mm × 22.3 mm × 180 mm test pieces (5 pieces) was heated to 180° C. Each of the inorganic coated sands of the above Examples and Comparative Examples was filled into the mold heated to 180° C. at a blow pressure of 0.3 MPa using a CSR-43 blow molding machine, and the inorganic coated sand was left to stand in the mold for 150 seconds to harden, thereby obtaining a mold test piece. (measurement) The mold strength (MPa) of each mold test piece was measured using a universal strength testing machine (PFG type) manufactured by George Fischer, which was previously equipped with a PBV flexural attachment. The mold test pieces were left in a constant temperature and humidity room (25°C / 55% RH) for 1 hour after being removed from the metal mold.
[0106] <Storability> Immediately after preparing each of the inorganic coated sands of the above Examples and Comparative Examples, 2 kg of the inorganic coated sand was placed in a plastic bag, sealed, and stored at 25°C for 12 hours. Immediately after that, mold test pieces were prepared in the same manner as in <Mold strength> above, and the mold strength was measured. The measurement results are shown in Table 2.
[0107] [Table 2]
Claims
1. A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic binder layer is composed of metasilicate hydrate and amorphous SiO 2 The inorganic coated sand contains fine particles, and the melt viscosity at 80°C of the inorganic binder constituting the inorganic binder layer is 32 mPa·s or more and 150 mPa·s or less.
2. A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic binder layer is made of metasilicate hydrate and amorphous SiO 2 An inorganic coated sand containing fine particles, the amount of water of hydration of the metasilicate hydrate being 6 or more and 8 or less.
3. A dry inorganic coated sand having a refractory aggregate and an inorganic binder layer covering a surface of the refractory aggregate, The inorganic binder layer is made of metasilicate hydrate and amorphous SiO 2 Contains fine particles, Inorganic coated sand having a fusion point of 40°C or higher and 60°C or lower, as determined by the JACT Test Method C-1 Fusion Point Test Method.
4. The inorganic coated sand according to any one of claims 1 to 3, The inorganic coated sand, wherein the inorganic binder layer contained in the inorganic coated sand is 0.2 parts by mass or more and 15 parts by mass or less per 100 parts by mass of the refractory aggregate.
5. The inorganic coated sand according to any one of claims 1 to 3, The amorphous SiO 2 The inorganic coated sand has a content of fine particles of 0.1 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the refractory aggregate.
6. A casting mold using the inorganic coated sand according to any one of claims 1 to 3.
7. An inorganic coated sand composition comprising the inorganic coated sand according to any one of claims 1 to 3.
8. A casting mold using the inorganic coated sand composition according to claim 7.
9. A method for producing the inorganic coated sand according to any one of claims 1 to 3, (1) mixing the refractory aggregate, metasilicate nonahydrate, and metasilicate pentahydrate to obtain a mixture; (2) cooling the mixture; Including, The step (1) comprises mixing the metasilicate nonahydrate and the metasilicate pentahydrate at a temperature equal to or higher than the melting point of the mixture, The step (2) comprises cooling the mixture of the metasilicate nonahydrate and the metasilicate pentahydrate to a temperature lower than the melting point of the mixture.
10. A method for producing the inorganic coated sand according to any one of claims 1 to 3, A method for producing inorganic coated sand, comprising the step (3) of mixing the refractory aggregate with a solution containing water glass, caustic alkali, and water to obtain a mixture containing metasilicate hydrate.
Citation Information
Patent Citations
Coil dismantling method in core of rotary machine
JP1978025803A
Inorganic coated sand
JP2020011296A
Coated sand, method for producing same, and method for producing casting mold using same
WO2018097180A1
